Pedro Calderon de la Barca: "El Tuzani de la Alpujarra o Amor despues de la muerte" - Devos, Brent W (University of Ottawa (Canada), 2007)
The purpose of the present study is to offer a faithful and readable text of El Tuzani de la Alpujarra o Amor despues de la muerte [The man named Tuzani of the Alpujarras mountains or Love after death], a play by Pedro Calderon de la Barca (1600--1681). This is an eclectic edition based on the editio princeps, the Quinta parte de comedias ('Barcelona' 1677), and corrected, when necessary, with the help of other early textual witnesses. The introduction includes a study of the alternate titles of the play, its probable date of composition, its early textual transmission, its staging in the 17th century, its polymetrical structure and the dramatic role of geography and toponymy. Included at the end of the edited text are a comprehensive set of explanatory notes as well as the textual variants of the fifteen early witnesses that were collated.
Keywords: Literature, Romance.; Theater.